Penentuan Daerah Thermal Front Di Laut Timur Su-matera Provinsi Riau - Panggabean, Santika; Mubarak, Mubarak; Ghalib, Musrifin (Jurnal Perikanan dan Kelautan, 2018)
This research was conducted from January to February 2017 in East Coastal of Riau Province. The main purpose of this study is to determine the distribution of sea surface temperature and determine the Thermal Front area.This research used spatial analysis method with Aqua Modis level 1 satellite image data processing. The software used is Modis Reprojection Tool Swath 2.2 and ArcGis 9.3. The result of this research is to know the distribution of sea surface temperature in east coastal waters of Su-matera Riau Province each month is different. Every month begins to decline from October to December.In October the temperature range foor 25-320C, in November is 24-320C and in December temperature is 22-320C.Thermal Front area results that are Each month detected differently based on the vulnerable sea surface temperatures SIED method wiht on a monthly basis. In October there are the eastern coast of Dumai, Bengkalis Regency, Meranti Islands, Estuary of kampar river and Indragiri Hilir Re-gency. In November there are on the eastern coast of Dumai and Bengkalis Regency. In December there are on East Coast of Bengkalis Regency, Kampar River Estuary and Indragiri Hilir Regency.